Rehabilitation of Wastewater Treatment Plant of Sakhnin City in Israel by Using Advanced Technologies - Avsar, Yasar; Tarabeah, Hussein; Kimchie, Shlomo; Ozturk, Izzet; Naamneh, Hadi (SPRINGER-VERLAG BERLIN, 2011)
This study deals with the rehabilitation of waste water treatment plant (WWTP) of Sakhnin city in Israel. To increase low removal efficiency of the facultative pond (FP) and seasonal reservoir (SR) of the WWTP, different kinds of reactors having different operating conditions were established by the name of two tasks such as intermittent trickling bio filters (ITBFs) and concrete tunnels, respectively. According to the evaluation of the results, it was observed that ITBFs and tunnel units contribute to reasonable removal capacity on sCOD, TSS, NH3-N and PO4-P parameters. When it is considered establishing a full scale treatment plant to rehabilitate FP and SR units of available WWTP, this study will be able to a guide for decision makers.
Keywords: Facultative; ITBF; Rehabilitation; WWTP; Environmental Sciences & Ecology